Multi-structure coordinated regulation efficient stable CsPbI3 nanorod as well as preparation method and application thereof

Through the improved thermal injection method, the amount of nitrate is adjusted to control the multi-structure of CsPbI3 nanorods, and the customization of its photoelectric characteristics and stability is achieved, and the problem of difficult regulation of the photoelectric characteristics and stability of CsPbI3 nanorods in the prior art is solved, and efficient and stable nanorods suitable for a variety of applications are prepared.

CN119505899APending Publication Date: 2025-02-25LIAONING UNIVERSITY

Patent Information

Application Number
CN202411805733.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to realize the coordinated multi-structure regulation of CsPbI3 nanorods, which makes it difficult to customize its photoelectric characteristics and stability, limiting its use in practical applications.

Method used

Through the improved thermal injection method, lead iodide, nitrate, oleic acid, oleamine and other substances are used to react under the protection of inert gas, and the amount of nitrate is adjusted to control the surface state, crystal plane, crystal phase and morphological structure of CsPbI3 perovskite, so as to achieve the regulation of luminescence peak position, fluorescence quantum efficiency, and carrier transport capacity.

Benefits of technology

The prepared CsPbI3 nanorod has excellent room temperature stability, high quantum efficiency and strong carrier transport capability, and is suitable for LEDs, solar cells, photodetectors and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505899A_ABST
    Figure CN119505899A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of luminescent materials, and provides a multi-structure coordinated regulation efficient stable CsPbI3 nanorod and a preparation method and application thereof.The preparation method comprises the following steps that octadecene, oleic acid and cesium carbonate are heated in the inert gas atmosphere and stirred till a solution is dissolved, and a precursor solution is obtained; the preparation method comprises the following steps: adding lead iodide, nitrate, oleic acid and oleylamine into a container filled with octadecene, exhausting gas, introducing inert gas, heating, and stirring to obtain a clear and transparent solution; heating, and injecting the precursor solution in the step 1 into the clear and transparent solution in the step 2; and carrying out heat preservation at first, then rapidly cooling to room temperature, and then centrifugally dispersing into a non-polar solvent to obtain the CsPbI3 nanorod. The method is simple to operate and low in energy consumption, and the red light CsPbI3 perovskite nanocrystal is stable in sample phase, narrow in half-peak width, high in luminous color purity, few in surface defect, high in quantum efficiency and high in carrier transport capacity, and can be applied to the fields of LEDs, solar cells, photoelectric detectors and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of luminescent materials, and in particular relates to highly efficient and stable CsPbI3 nanorods with coordinated multi-structure regulation, and a preparation method and application thereof. Background Art

[0002] Cesium lead halide perovskite (CsPbX3, X = Cl, Br, I) is a new semiconductor light-emitting material with excellent optoelectronic properties, such as high photoluminescence quantum yield (PLQYs), adjustable band gap and excellent optoelectronic transport performance, and has therefore been widely studied. Among them, CsPbI3 nanocrystals (NCs) have attracted great attention due to their small carrier effective mass and narrow direct band gap. In addition, CsPbI3 NCs have rich structures, such as surface state structure, crystal plane structure, lattice structure (crystalline phase structure) and morphology structure, which have a great influence on the optoelectronic properties and stability of CsPbI3 NCs and can significantly regulate their quantum efficiency, band gap, exciton binding energy, carrier transport capacity and stability. However, it is currently impossible to achieve precise structural regulation of the optoelectronic properties and stability of perovskites, and it is impossible to customize CsPbI3 NCs with specific optics, electrical and stability, which greatly limits their practical applications. Therefore, exploring the regulation rules of the structure in CsPbI3 NCs on the photoelectric properties and stability of CsPbI3 NCs is of great significance for the preparation of efficient and stable CsPbI3 NCs.

[0003] At present, there is little public research on the synthesis of CsPbI3 nanorods, and there is even less research on efficient and stable CsPbI3 nanorods with multi-structure coordinated regulation and their application in LEDs. Summary of the invention

[0004] The purpose of the embodiments of the present invention is to provide a method for preparing highly efficient and stable CsPbI3 nanorods with coordinated multi-structure regulation, aiming to solve the problems raised in the above-mentioned background technology.

[0005] The embodiment of the present invention is achieved by a method for preparing a highly efficient and stable CsPbI3 nanorod with multi-structure coordinated regulation, comprising the following steps: Step 1: heating octadecene, oleic acid and cesium carbonate under an inert gas atmosphere and stirring until the solution is dissolved to obtain a precursor solution; Step 2: Add lead iodide, nitrate, oleic acid and oleylamine into a container containing octadecene, evacuate the air, then introduce an inert gas, heat and stir to obtain a clear and transparent solution; Step 3: Raise the temperature and inject the precursor solution in step 1 into the clear and transparent solution in step 2; Step 4: first keep warm, then quickly cool to room temperature, and then disperse into a non-polar solvent by centrifugation to obtain the CsPbI3 nanorods.

[0006] Preferably, in step 1, the volume ratio of octadecene to oleic acid is 10:1, and the concentration of cesium carbonate is 0.04 g / mL.

[0007] Preferably, in step 1, the stirring speed is 800 rad and the stirring time is 40 min.

[0008] Preferably, in step 2, the volume ratio of octadecene, oleic acid and oleylamine is 5:1:1, and the molar ratio of nitrate and lead iodide is 0.2-1:1.

[0009] Preferably, in step 2, the inert gas is N2, and the stirring time is 30 min.

[0010] Preferably, in step three, the volume ratio of the precursor solution to the clear and transparent solution is 1:14.

[0011] Preferably, in step 4, the insulation time is 15 seconds.

[0012] Preferably, in step 4, the rotation speed of the centrifugal dispersion is 9000-10000 rad, and the non-polar solvent is cyclohexane.

[0013] Another object of an embodiment of the present invention is to provide a highly efficient and stable CsPbI3 nanorod with multi-structure coordinated regulation, which is prepared by the above-mentioned preparation method.

[0014] Another object of an embodiment of the present invention is to provide an application of a multi-structure coordinated and highly efficient and stable CsPbI3 nanorod in the preparation of an electroluminescent LED device, wherein the CsPbI3 nanorod serves as a light-emitting layer.

[0015] The preparation method of the multi-structure coordinated and regulated efficient and stable CsPbI3 nanorods provided in the embodiment of the present invention adopts a modified hot injection method to fully dissolve lead iodide and nitrate in an octadecene solvent mixed with surfactants oleic acid and oleylamine under the protection of an inert gas, so that the Pb atoms and I atoms are fully in contact with the surfactant, zinc ions, and nitrate ions. After reacting for a period of time at a certain temperature, the precursor Cs source is injected, and then the Cs source gradually nucleates with the lead iodide and nitrate solution in the process. The surface state of the CsPbI3 perovskite is controlled by adjusting the amount of nitrate, exposing the crystal plane, crystal phase and morphology structure, realizing the regulation of the luminescence peak position, fluorescence quantum efficiency, and carrier transport capacity. The prepared CsPbI3 nanorods have excellent room temperature stability; This preparation method is simple to operate, low in energy consumption, and has high development value. The red light CsPbI3 perovskite nanocrystal sample prepared by this preparation method has stable phase, narrow half-peak width, high luminescent color purity, few surface defects, high quantum efficiency and strong carrier transport capacity, and can be used in LEDs, solar cells, photodetectors and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 TEM images of samples prepared in Examples 1-3 and Comparative Example 1 of the present invention; Figure 2 XRD images of samples prepared in Examples 1-3 and Comparative Example 1 of the present invention; Figure 3 Photoluminescence (PL) spectra of samples prepared in Examples 1-3 and Comparative Example 1 of the present invention; Figure 4 The PLQY results of the samples prepared in Examples 1-3 and Comparative Example 1 of the present invention are shown below; Figure 5 The carrier transport characteristics of the samples prepared in Example 1 and Comparative Example 1 of the present invention are shown in FIG. Figure 6 (1) is the stability results of the samples prepared in Example 1 of the present invention and Comparative Example 1, Figure 6 (2) The stability results of the samples when applied in LED devices. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0018] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0019] Example 1: A highly efficient and stable CsPbI3 nanorod with multi-structure coordinated regulation, the preparation method of which comprises the following steps: Step 1: Add 10 mL of octadecene, 1 mL of oleic acid, and 0.4 g of cesium carbonate into a 50 mL three-necked bottle, heat to 120 ° C under N2 atmosphere, and stir the solution until it dissolves and turns light yellow to obtain a precursor solution for use in the following steps; Step 2: Add 0.3 mmol lead iodide, 2 mL oleic acid, 2 mL oleylamine, and 0.3 mmol Zn(NO3)2 into a three-necked bottle containing 10 mL octadecene, evacuate for 30 min, then introduce inert gas N2, heat to 120°C and stir for 40 min to obtain a clear and transparent solution; Step 3: Raise the temperature to 165°C, and inject 1 mL of the precursor from step 1 into the clear and transparent solution from step 2; Step 4: Maintain at 165° C. for 15 seconds and quickly cool to room temperature using an ice-water bath, then disperse into 2 mL of cyclohexane by centrifugation to obtain α-CsPbI3 nanorods.

[0020] Example 2: A highly efficient and stable CsPbI3 nanorod with multi-structure coordinated regulation, the preparation method of which comprises the following steps: Step 1: Add 10 mL of octadecene, 1 mL of oleic acid, and 0.4 g of cesium carbonate into a 50 mL three-necked bottle, heat to 120 ° C under N2 atmosphere, and stir the solution until it dissolves and turns light yellow to obtain a precursor solution for use in the following steps; Step 2: Add 0.3 mmol lead iodide, 2 mL oleic acid, 2 mL oleylamine, and 0.15 mmol Zn(NO3)2 into a three-necked bottle containing 10 mL octadecene, evacuate for 30 min, then introduce inert gas N2, heat to 120°C and stir for 40 min to obtain a clear and transparent solution; Step 3: Raise the temperature to 165°C, and inject 1 mL of the precursor from step 1 into the clear and transparent solution from step 2; Step 4: Maintain at 165° C. for 15 seconds and quickly cool to room temperature using an ice-water bath, then disperse into 2 mL of cyclohexane by centrifugation to obtain α-CsPbI3 nanorods.

[0021] Example 3: A highly efficient and stable CsPbI3 nanorod with multi-structure coordinated regulation. The preparation method thereof is different from that of Example 1, except that the amount of Zn(NO3)2 in step 2 is 0.075 mmol, and other conditions remain the same.

[0022] Example 4: A highly efficient and stable CsPbI3 nanorod with multi-structure coordinated regulation. The preparation method thereof is different from that of Example 1, except that the temperature is raised to 155°C in step 3, and other conditions remain the same.

[0023] Example 5: A highly efficient and stable CsPbI3 nanorod with multi-structure coordinated regulation. The preparation method thereof is different from that of Example 2, except that the temperature is raised to 160°C in step 3, and other conditions remain the same.

[0024] Example 6: A highly efficient and stable CsPbI3 nanorod with multi-structure coordinated regulation. The preparation method thereof is different from that of Example 2, except that the temperature is raised to 170°C in step 3, and other conditions remain the same.

[0025] Comparative Example 1: A CsPbI3 nanomaterial, the preparation method of which comprises the following steps: Step 1: Add 10 mL of octadecene, 1 mL of oleic acid, and 0.4 g of cesium carbonate into a 50 mL three-necked bottle, heat to 120 ° C under N2 atmosphere, and stir the solution until it dissolves and turns light yellow to obtain a precursor solution for use in the following steps; Step 2: Add 0.3 mmol lead iodide, 2 mL oleic acid and 2 mL oleylamine into a three-necked bottle containing 10 mL octadecene, evacuate for 30 min, then introduce inert gas N2, heat to 120°C and stir for 40 min to obtain a clear and transparent solution; Step 3: Raise the temperature to 165°C, and inject 1 mL of the precursor from step 1 into the clear and transparent solution from step 2; Step 4: Maintain at 165°C for 15 seconds and quickly cool to room temperature using an ice-water bath, then disperse into 2 mL of cyclohexane by centrifugation to obtain γ-CsPbI3.

[0026] Performance Testing: The samples prepared in Examples 1-3 and Comparative Example 1 were analyzed using a transmission electron microscope, and the TEM images were as follows: Figure 1 As shown, according to Figure 1 It can be seen that a certain amount of zinc nitrate can promote the formation of efficient and stable CsPbI3 nanorods, but too little is not conducive to obtaining stable CsPbI3 nanorods. The morphology of the orthorhombic phase CsPbI3 (γ-CsPbI3) prepared without adding Zn(NO3)2 is nanocubic blocks (such as Figure 1 As shown in a), compared with the addition of 0.075mmol and 0.15mmol Zn(NO3)2, the CsPbI3 obtained by adding 0.3mmol Zn(NO3)2 has a nanorod morphology (as shown in Figure 1 d); The samples prepared in Examples 1-3 and Comparative Example 1 were analyzed using an X-ray diffractometer, and the XRD patterns were as follows: Figure 2 As shown, according to Figure 2 It can be seen that the nanocrystals prepared by adding 0.3mmol Zn(NO3)2 are cubic phase CsPbI3 (α-CsPbI3); The samples prepared in Examples 1-3 and Comparative Example 1 were analyzed using a spectrometer to obtain photoluminescence (PL) spectra as shown in Figure 3 As shown, according to Figure 3 It can be seen that with the increase of Zn(NO3)2, the emission peak undergoes an obvious blue shift; The quantum efficiency (PLQY) results of the samples prepared in Examples 1-3 and Comparative Example 1 were obtained by using a photoluminescence quantum efficiency measurement system. Figure 4 As shown, according to Figure 4It can be seen that the quantum efficiency increases with the increase of Zn(NO3)2; The samples prepared in Example 1 and Comparative Example 1 were analyzed by IV test, and the carrier transport characteristics were obtained as follows: Figure 5 As shown, according to Figure 5 It can be seen that the carrier transport of the α-CsPbI3 nanorods prepared in Example 1 is accelerated.

[0027] The stability of the samples prepared in Example 1 and Comparative Example 1 was analyzed, and Example 1 and Comparative Example 1 were used as light-emitting layers to prepare electroluminescent LED devices, and the stability of the devices was analyzed. The results are as follows: Figure 6 As shown, according to Figure 6 It can be seen that the stability of the α-CsPbI3 nanorods prepared in Example 1 can reach 180 days, while the stability of the γ-CsPbI3 prepared in Comparative Example 1 is only 30 days. When applied to LED devices, the stability of the α-CsPbI3 nanorods is nearly 5 times higher than that of the γ-CsPbI3 nanorods.

[0028] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing highly efficient and stable CsPbI3 nanorods with multi-structure coordinated regulation, characterized in that: The following steps are involved: Step 1: heating octadecene, oleic acid and cesium carbonate under an inert gas atmosphere and stirring until the solution is dissolved to obtain a precursor solution; Step 2: Add lead iodide, nitrate, oleic acid and oleylamine into a container containing octadecene, evacuate the air, then introduce an inert gas, heat and stir to obtain a clear and transparent solution; Step 3: Raise the temperature and inject the precursor solution in step 1 into the clear and transparent solution in step 2; Step 4: first keep warm, then quickly cool to room temperature, and then disperse into a non-polar solvent by centrifugation to obtain the CsPbI3 nanorods.

2. The preparation method according to claim 1, characterized in that: In step 1, the volume ratio of octadecene to oleic acid is 10:1, and the concentration of cesium carbonate is 0.04 g / mL.

3. The preparation method according to claim 1, characterized in that: In step 1, the stirring speed is 800 rad and the stirring time is 40 min.

4. The preparation method according to claim 1, characterized in that: In step 2, the volume ratio of octadecene, oleic acid and oleylamine is 5:1:1, and the molar ratio of nitrate and lead iodide is 0.2-1:

1.

5. The preparation method according to claim 1, characterized in that: In step 2, the inert gas is N2, and the stirring time is 30 minutes.

6. The preparation method according to claim 1, characterized in that: In step 3, the volume ratio of the precursor solution to the clear and transparent solution is 1:

14.

7. The preparation method according to claim 1, characterized in that: In step 4, the insulation time is 15s.

8. The preparation method according to claim 1, characterized in that: In step 4, the rotation speed of the centrifugal dispersion is 9000-10000 rad, and the non-polar solvent is cyclohexane.

9. A highly efficient and stable CsPbI3 nanorod with multi-structure coordinated regulation, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.

10. An application of the multi-structure coordinated and highly efficient and stable CsPbI3 nanorods as claimed in claim 9 in the preparation of electroluminescent LED devices, characterized in that: The CsPbI3 nanorods serve as a light-emitting layer.

Citation Information

Patent Citations

  • Efficient and stable cubic phase CsPbI3 nanocrystal passivated by calcium nitrate and preparation method of cubic phase CsPbI3 nanocrystal

    CN113736459A

  • Preparation method of nanocrystalline based on blue-violet light

    CN113861974A

Cited By

  • Method for regulating morphology structure of perovskite quantum dot material

    CN120248879A